Numerical Modeling of the Aluminum Alloy AW5083 Using Large-Strain Thermo-Elasto-Plasticity - Sobierańska, Agnieszka; Wcisło, Balbina (Engineering Transactions, 2026)
This paper deals with the constitutive modeling and finite element (FE) simulations of advanced models related to large-strain thermo-elasto-plastic behavior of aluminum alloy AW5083, which can reproduce the material response at different temperatures from room temperature up to 500 °C. Significant focus is placed on internal sources of cooling and heating resulting from thermo-elastic and thermo-plastic couplings, respectively, and on the influence of elevated temperature on these couplings. The formulation of the constitutive description is based on a thermodynamic approach. Two models are presented and tested, including temperature-dependent and temperature-independent plastic free energy function. Numerical tests of the developed models are carried out for a uniaxial tensile test. For the sake of comparison with experimental results, a dogbone specimen examined in a tensile machine is analyzed.